SnO2 dense ceramic microwave sintered with low resistivity - Perazolli, Leinig Antonio [UNESP]; Gasparotto, Gisane [UNESP]; Jaomaci, Natalia [UNESP]; Ruiz, Miguel [UNESP]; Zaghete, Maria Aparecida [UNESP]; Foschini, Cesar Renato [UNESP]; Aguiar, Ederson Carlos [UNESP]; Varela, José Arana [UNESP] (Scientific Research Publishing, 2012)
The Hall-Héroult process is used for alumina reduction by the use of graphite anodes even though it involves a high emission of carbon dioxide (CO2) and several other organic compounds. Proposals have been made aiming at substitut- ing graphite for a single-phase SnO2-based ceramic with low resistivity and chemical resistance to cryolite, which is characterized as an inconsumable anode, reducing pollutant emissions. To this end, a wide range of studies were carried out on SnO2-based ceramics modified with ZnO as a densification aid doped with the promoters of electrical conduc- tivity such as Nb2O5, Al2O3 and Sb2O3 through a mixture of oxides and hybrid sintering in a microwave oven. The pressed pellets were sintered in a microwave oven up to 1050°C under a constant heating rate of 10°C/min. After sin- tering, the density was determined by the Archimedes method, the phases were then characterized by X-ray diffraction, the microstructure and chemical composition resulting from the sintered SnO2-based ceramics were also investigated by field emission scanning electron microscopy (FE-SEM) coupled with an energy-dispersive X-ray spectroscopy (EDS) and the electrical properties were determined by the measurements of the electric field × current density. A single-phase ceramic was obtained with a relative density of above 90% and electrical resistivity of 6.1 Ω·cm at room temperature. The ceramics obtained in this study could be a potential candidate as an inconsumable anode to replace the current fused coke used in the reduction of alumina.
Keywords: Tin Oxide; Anodic Electrode; Inconsumable Anode; Microwave Sintering; Electrical Resistivity